Grain Legumes 2016
DOI: 10.5772/64911
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Control of Cadmium Concentration in Soybean Seeds

Abstract: Cadmium (Cd) is a chemical element present in the soil. At high concentrations Cd can cause physiological and morphological damages to plants and it is highly toxic to human beings. Minimizing the intake of Cd and other heavy metals from food consumption is an important health issue. Efforts have been made to identify genetic elements that are involved in Cd detoxification in plants. Heavy metal transporter 3 (HMA3) plays a role in sequestration of Cd into vacuoles in soybean (Glycine max). Inheritance studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 92 publications
(129 reference statements)
1
6
0
1
Order By: Relevance
“…those showing a moderate Cd accumulation (D8<D3<D2<D15 < D14 < D11), and other ones with considerably higher Cd accumulation in beans. This suggests the predominantly genetic origin of these differences, which is in line with other observations (Arao et al, 2003) further confirmed (Ishikawa et al, 2005) and developed (Kobori et al, 2011), and some genetic/ genomic studies (Jegadeesan et al, 2016).…”
Section: Occurrence and Role Of Seed (Bean) Enrichment/protection Mecsupporting
confidence: 88%
See 2 more Smart Citations
“…those showing a moderate Cd accumulation (D8<D3<D2<D15 < D14 < D11), and other ones with considerably higher Cd accumulation in beans. This suggests the predominantly genetic origin of these differences, which is in line with other observations (Arao et al, 2003) further confirmed (Ishikawa et al, 2005) and developed (Kobori et al, 2011), and some genetic/ genomic studies (Jegadeesan et al, 2016).…”
Section: Occurrence and Role Of Seed (Bean) Enrichment/protection Mecsupporting
confidence: 88%
“…Besides, the major role of genetic control of Cd concentrations in soybean seeds (Jegadeesan et al, 2016) also seems to be limited. These limitations were illustrated by the high 0.5<SAF Sh !1.0 values assessed for all tested cultivars grown in moderately Cd-polluted soil, which indicated low or lacking seed protection, up to excessive accumulation of Cd in seeds.…”
Section: Decisive Factors In CD Accumulation In Soybean Seeds (Beans)mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates the presence of additional genetic factors regulating Cd in soybean seed; identification of such factors in appropriate mapping populations could contribute to a further reduction of Cd accumulation. More details on the genetic control of Cd accumulation in soybean and marker-based selection have recently been summarized by JEGADEESAN et al (2016). As there are various sources of Cd pollution to agricultural soils, ionomics and genomics assisted breeding could make important contributions to mitigating the risks of Cd toxicity and to enhancing food safety.…”
Section: Ionomics Of Soybean Cadmium Accumulationmentioning
confidence: 99%
“…Cadmium is one of the chemical elements present in the soil in high concentrations and can cause physiological and morphological damage to plants. It is also highly toxic to humans [11]. Because of its high mobility and toxicity at low concentrations in plants, it is also toxic to the environment [12].…”
Section: Introductionmentioning
confidence: 99%